Ambient air pollution exposure in relation to cerebral small vessel disease in Chinese population: A cranial magnetic resonance imaging-based study - Yudiyang Ma; Ying Hui; Linxi Tang; Jianing Wang; Meiqi Xing; Lei Zheng; Feipeng Cui; Shuohua Chen; Shouling Wu; Zhenchang Wang; Yaohua Tian (Eco-Environment & Health)
Cerebral small vessel disease (CSVD), a chronic and progressive vascular disorder closely associated with stroke and dementia, is primarily identified and diagnosed in cranial magnetic resonance imaging (MRI). Given the limited evidence on the relationship between air pollution and CSVD, this study aimed to investigate the links between multiple air pollutants exposure and CSVD risk. Eligible subjects and their cranial MRI data were obtained from the Multi-modality Medical Imaging Study Based on Kailuan Study, totaling 1216 participants. Ordinal and binary logistic regression models were utilized to evaluate the associations between air pollution exposure and the neuroimaging markers of CSVD. For each interquartile range increase in air pollutant exposure during the examination year, the odds ratios and 95% confidence intervals of the increased white matter hyperintensity burden were 1.45 (1.15, 1.84) for PM2.5, 1.72 (1.27, 2.34) for PM10, 1.26 (1.05, 1.51) for SO2, 1.52 (1.16, 2.00) for NO2, and 1.63 (1.26, 2.13) for CO. The results remained consistent even when the model was fitted using air pollution from different exposure windows. Furthermore, the estimated effect sizes for the total burden of CSVD were 1.20 (1.01, 1.43) for PM2.5, 1.39 (1.12, 1.74) for PM10, 1.26 (1.03, 1.53) for NO2, and 1.30 (1.08, 1.58) for CO. These findings suggest that a positive link between air pollutants exposure and neuroimaging markers of CSVD in the Chinese population, revealing the importance of controlling environmental pollutants to protect the population against cerebral small vessel damage.